The Minimalist Program and the Origin of Language: A View From Paleoanthropology - Tattersall, Ian (Frontiers in Psychology, 2019)
In arguing that articulate language is underpinned by an algorithmically simple neural operation, the Minimalist Program (MP) retrodicts that language emerged in a short-term event. Because spoken language leaves no physical traces, its ancient use must be inferred from archaeological proxies. These strongly suggest that modern symbolic human behavior patterns – and, by extension, cognition – emerged both abruptly and late in time (subsequent to the appearance of Homo sapiens as an anatomical entity some 200 kyr ago). Because the evidence is compelling that language is an integral component of modern symbolic thought, the archaeological evidence clearly supports the basic tenet of the MP. But the associated proposition that language was externalized in an independent event that followed its initial appearance as a conduit to internal thought, is much more debatable.